Fractionation and Characterization of Tannin Acyl Hydrolase from Aspergillus niger - YUNITA ARIAN SANI ANWAR; I MADE ARTIKA; HASIM DANURI (Bogor Agricultural University, Indonesia, 2009)
We previously produced tannin acyl hydrolase (tannase) from Aspergillus niger isolated from cacao pod. In the present study the enzyme was subjected to fractionation by ammonium sulphate followed by dialysis process. The saturation level of ammonium sulphate used was 30-80% where the best enzyme activity was obtained at the saturation level of 60%. Compared to that of crude enzyme, specific activity of tannase after dialysis was four folds. Characterization results showed that optimum activity was at 35-50 oC and pH 6. Tannase was activated by K+ and Na+ at concentration of 0.01 and 0.05 M respectively. Mg2+ was found activate tannase only at 0.01 M. Addition of metal ions like Zn2+, Cu2+, Ca2+, Mn2+ and Fe2+ inhibited the enzyme activity. Kinetics analysis of various substrates tested showed that the Km value of tannic acid and gallotannin was 0.401 and 6.611 mM respectively. Vmax value of tannic acid was 10.804 U/ml and of gallotannin was 12.406 U/ml. Based on Michaelis-Menten constant (Km), the tannase obtained in the present study was more active in hydrolysing depside bonds rather than ester bonds. Key words: tannase, fermentation, fractionation, characterization, Aspergillus niger